Molecular pathways of pannexin1-mediated neurotoxicity - Shestopalov, Valery I.; Slepak, Vladlen Z. (Frontiers in Physiology, 2014)
Pannexin1 (Panx1) forms non-selective membrane channels, structurally similar to gap junction hemichannels, and are permeable to ions, nucleotides, and other small molecules below 900 Da. Panx1 activity has been implicated in paracrine signaling and inflammasome regulation. Recent studies in different animal models showed that overactivation of Panx1 correlates with a selective demise of several types of neurons, including retinal ganglion cells, brain pyramidal, and enteric neurons. The list of Panx1 activators includes extracellular ATP, glutamate, high K+, Zn2+, fibroblast growth factors (FGFs),pro-inflammatory cytokines, and elevation of intracellular Ca2+. Most of these molecules are released following mechanical, ischemic, or inflammatory injury of the CNS, and rapidly activate the Panx1 channel. Prolonged opening of Panx1 channel induced by these “danger signals” triggers a cascade of neurotoxic events capable of killing cells. The most vulnerable cell type are neurons that express high levels of Panx1. Experimental evidence suggests that Panx1 channels mediate at least two distinct neurotoxic processes: increased permeability of the plasma membrane and activation of the inflammasome in neurons and glia. Importantly, both pharmacological and genetic inactivation of Panx1 suppresses both these processes, providing a marked protection in several disease and injury models. These findings indicate that external danger signals generated after diverse types of injuries converge to activate Panx1. In this review we discuss molecular mechanisms associated with Panx1 toxicity and the crosstalk between different pathways.